Optimization Of Regional Financial Management For Sustainable Development - Alim, Rizky Zainul; Djasuli, Mohammad (Dinasti International Journal of Economics, Finance & Accounting, 2024)
Optimization of regional financial management is an activity that includes planning, budgeting, implementation, administration, reporting, accountability, and supervision of regional finances. This research aims to identify, analyze, and provide recommendations regarding the optimization of regional financial management in order to support sustainable development. This type of research is library research, which is research that uses literature, books, magazines, journals, or other references in collecting in-depth information and data. Overall, optimizing regional financial management through the implementation of transparency, accountability, increasing the capacity of the apparatus, community participation, and effective supervision are crucial steps to support sustainable development.